PEDAGANG DALAM SEJARAH DAKWAH DI NUSANTARA - sarwan sarwan (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2006)
Traditional trade relationship between the Indonesian people and the people who live in the Middle East had been existed since the era when The Prophet of Muhammad Saw. was born, which most of the people were animism. Meanwhile, the people who were Moslems came to Indonesia. From these merchants, Islam was introduced to Indonesian people. Besides, from them “dakwah islamiyah” was begun and spread from one harbour to the others. This effort then was continued by the “ulama” and generally by other Islam kingdoms.